How assertive behavior differences among Minang, Malay, Batak and Kerinci student’s culture? - Afdal, Afdal; Wibowo, Tianda Hazmil; Alfia, Vivi; Maysitoh, Maysitoh (COUNS-EDU: The International Journal of Counseling and Education, 2019)
The attitude of students who cannot convey what they feel without hurting the feelings of others is because the student cannot behave assertively. Assertive behavior is expressing what is felt or thought without hurting the feelings of others. This study aims to see differences in assertive behavior of students based on cultural backgrounds (Minang, Malay, Batak, Kerinci). This study uses a comparative descriptive approach carried out on BK FIP UNP students with a total sample of 248 people, using a proportional random sampling technique. The instrument of this research is a questionnaire about assertive behavior with a Likert scale model. Data were analyzed using analysis of variance (ANOVA) and data processing using SPSS version 20.00. The findings of this study indicate that there is no significant difference in assertive behavior of BK FIP UNP students when viewed from a cultural background. This means that differences in cultural background do not determine student assertive behavior. This is indicated by the calculated F value, which is equal to 0.779 while Sig. on the degree of freedom (db) 1 and aplha (?) 0.05 is 0.506, then according to hypothesis testing criteria through analysis of variance (ANOVA), if F count is greater than F table there is no significant difference.